Force of infection and evolution of lesions of canine tegumentary leishmaniasis in northwestern Argentina - Marco, Jorge Diego (2001)
A clinical-serological follow-up was carried out in a canine population in endemic foci of Leishmania braziliensis spread in northwestern Argentina. Each dog was studied in at least two visits, 309±15 days (X±SE) apart. Some initially healthy dogs (n=52) developed seroconversion or lesions. The clinical evolution of the disease in dogs resembles in many aspects the human disease. Similarities include the long duration of most ulcers with occasional healing or appearance of new ones and the late appearance of erosive snout lesions in some animals. Yearly incidence rates of 22.7% for seroconversion and of 13.5% for disease were calculated as indicators of the force of infection by this parasite upon the canine population.